Paternal Deprivation and Female Biparental Family Rearing Induce Dendritic and Synaptic Changes in Octodon degus: I. Medial Prefrontal Cortex - de Schultz, Tony; Bock, Joerg; Braun, Katharina (Frontiers in Synaptic Neuroscience, 2020)
In most mammalian species parent-offspring interactions during early life periods primarily comprise social contacts with the mother, whereas the role of males in parental care is one of the most overlooked and understudied topics. The present study addressed the hypothesis that the complete deprivation of paternal care delays or permanently retards synaptic connectivity in the brain, particularly the medial prefrontal cortex (mPFC) of the offspring in a sex-specific manner. Another aim of this study was to address the question whether and in which way replacing the father with a female caregiver (in our experiments the “aunt”) can “buffer” the detrimental effects of paternal deprivation on neuronal development. The comparison of a) single mother rearing, b) biparental rearing by father and mother and c) biparental rearing by two female caregivers revealed that i) paternal care represents a critical environmental factor for synaptic and dendritic development of pyramidal neurons in the vmPFC of their offspring; ii) a second female caregiver (“aunt”) does not “buffer” the neuronal consequences of paternal deprivation and that iii) neuronal development in the vmPFC is differentially affected in male and female offspring in response to different family constellations.